AC conductivity of binary silver phosphate glasses - Chow, Sai Pew; Shaari, Abdul Halim; Leong, M. L.; Yow, H. K.; Abd. Aziz, Sidek; Hassan, Senin (IEEE, 1998)
Samples of binary silver phosphate glasses with composition (Ag2O)x(P2O5)1-x have been prepared and their ac electrical conductivities measured over a range of frequency, composition and temperature. It is observed that a.c. conductivity increases very gradually at low frequency (below 1 kHz), but rapidly at higher frequency (above 10 kHz). Conductivity as high as 10-5 Scm-1 has been observed depending on the composition, frequency and temperature of the samples. It increases almost linearly with the mole fraction of Ag2O. As a function of temperature, the conductivity increases too with temperature. Arrhenius plot is obeyed and activation energy of 0.41 to 0.46 eV has been obtained.